2006
DOI: 10.1256/qj.05.42
|View full text |Cite
|
Sign up to set email alerts
|

The formation of hurricaneHumberto (2001): The importance of extra-tropical precursors

Abstract: SUMMARYThe authors examine the formation of hurricane Humberto (2001) in the Atlantic basin. Precursor disturbances originating in the extratropics appear critical for inducing tropical cyclogenesis. One precursor near the tropopause arose during the development of hurricane Erin on 7 September and could be tracked continuously for 12 days until 1200 UTC 19 September. A fully explicit numerical simulation with the PSU/NCAR mesoscale model produces a generally realistic evolution of the developing storm during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 46 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…For the 7 days prior to the formation of Peipah, SSTs and vertical wind shear provided favorable environments for tropical transition (Davis & Bosart, , , ; Sadler, , , ). In Figure a, pre‐Peipah remained over regions where SST exceeded 26 °C.…”
Section: Resultsmentioning
confidence: 99%
“…For the 7 days prior to the formation of Peipah, SSTs and vertical wind shear provided favorable environments for tropical transition (Davis & Bosart, , , ; Sadler, , , ). In Figure a, pre‐Peipah remained over regions where SST exceeded 26 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In a sheared environment, the mid‐level, mesoscale convective vortex (MCV) is advected downstream from the surface vortex, and the two must remain dynamically coupled for development to proceed. The low‐level vortex can slowly intensify by building upwards [e.g., Davis and Bosart , 2006; Tory et al , 2007]; or a new low‐level vortex can form underneath the mid‐level vortex as a result of a large burst of convection, the so called “down‐shear reformation” [ Molinari et al , 2006].…”
Section: Discussionmentioning
confidence: 99%
“…In high‐resolution experiments with the Weather Research and Forecasting model, Davis and Bosart [, ] and Nolan [] provided more concrete evidence about the necessity of an upper level warm core and a midlevel vortex for the RI onset. By tracking the evolution of moist convection within the inner core region of an idealized storm, Nolan [] demonstrated that convective bursts could moisten the low‐to‐middle level troposphere gradually for a period of several days.…”
Section: Introductionmentioning
confidence: 99%
“…The intensification can be further enhanced if the initial vortex has a larger vertical extent to upper levels. This is consistent with the analysis obtained from the real‐time experiments by Davis and Bosart [], which also revealed that both a midlevel vortex and a near‐saturated inner core from the surface to 500 hPa were required for the genesis of Hurricane Diana (1984).…”
Section: Introductionmentioning
confidence: 99%